2022
DOI: 10.1186/s13244-022-01339-9
|View full text |Cite
|
Sign up to set email alerts
|

Reperfusion injury on computed tomography following endovascular revascularization of acute mesenteric ischemia: prevalence, risk factors, and patient outcome

Abstract: Background Data about reperfusion injury (RI) following acute arterial mesenteric ischemia (AAMI) in humans are scarce. We aimed to assess the prevalence and risk factors of RI following endovascular revascularization of AMI and evaluate its impact on patient outcomes. Methods Patients with AAMI who underwent endovascular revascularization (2016–2021) were included in this retrospective cohort. CT performed < 7 days after treatment was reviewed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…This bull's-eye appearance is similar to venous ischemic bowel wall changes, and similarly, also fat stranding and peritoneal fluid can be observed [14]. Reperfusion phenomena are not necessarily associated with patients' worsening and can also occur after a successful revascularization [17,65].…”
Section: Bowel Findingsmentioning
confidence: 79%
“…This bull's-eye appearance is similar to venous ischemic bowel wall changes, and similarly, also fat stranding and peritoneal fluid can be observed [14]. Reperfusion phenomena are not necessarily associated with patients' worsening and can also occur after a successful revascularization [17,65].…”
Section: Bowel Findingsmentioning
confidence: 79%
“…14 Recent research has shown that the 3-month survival after reperfusion between those showing reperfusion injury did not differ from those without findings of reperfusion injury. 16 Imaging findings that can be seen with reperfusion injury include hyperenhancing bowel, bowel wall thickening, ascites, and mesenteric fat stranding.…”
Section: Reperfusionmentioning
confidence: 99%
“…Reperfusion injury can lead to shock, disseminated intravascular dissemination, or multiorgan failure, but is associated with an overall better prognosis and decreased mortality than inadequately reperfused bowel 14. Recent research has shown that the 3-month survival after reperfusion between those showing reperfusion injury did not differ from those without findings of reperfusion injury 16…”
Section: Cause-specific Imaging Findings Of Acute Mesenteric Ischemiamentioning
confidence: 99%
“…A study by Garzelli et al in 2022 demonstrated that reperfusion injury could be a frequent complication of endovascular revascularization of AMI, especially in those who present with decreased bowel wall enhancement on pretreatment CT, anabolic cause, and complete occlusion of the superior mesenteric artery [33]. However, it does not seem to impact short-term survival negatively [33].…”
Section: Endovascular Revascularizationmentioning
confidence: 99%